Minds online teaching effectively with technology - Miller, Michelle D. (Cambridge, Massachusetts Harvard University Press, 2014)
"From wired campuses to smart classrooms to massive open online courses (MOOCs), digital technology is now firmly embedded in higher education. But the dizzying pace of innovation, combined with a dearth of evidence on the effectiveness of new tools and programs, challenges educators to articulate how technology can best fit into the learning experience. Minds Online is a concise, nontechnical guide for academic leaders and instructors who seek to advance learning in this changing environment, through a sound scientific understanding of how the human brain assimilates knowledge."
Chapter 1 Is online learning here to stay? -- Chapter 2 Online learning: does it work? -- Chapter 4 Attention -- Chapter 5 Memory -- Chapter 6 Thinking -- Chapter 7 Incorporating multimedia effectively -- Chapter 8 Motivating students -- Chapter 9 Putting it all together.
Includes bibliographical references and index.
Keywords: Computer-assisted instruction; Educational technology; Internet in education; Learning, Psychology of; Teaching -- Computer network resources; Online learning